Early Language Reading Interventions and Reading Skills of Elementary Grade One Pupils in Zambales, Philippines - Mejala, Jennifer R. (Future Science / FSH-PH Publications, 2024)
Learning to read and write is crucial in child’s development during entering formal schooling in grade one. These skills are identified to as language and literacy skills. It also predicts the child’s success later in school as well as in life. Reading and writing were both encompassed in early language literacy which are the foundation skills of a child and it develops as the child grows. This study aimed to determine the effects of the reading intervention strategies used by grade one teachers on the reading performance of grade one pupils in terms of word recognition, reading speed and reading comprehension. The participants in this study were the 23 grade one teachers coming from the 11 schools of the San Antonio District. Findings of the study came up with the following conclusions: Typical teachers of Grade I in San Antonio always use reading intervention strategies in terms of oral language, alphabet knowledge and word recognition, and often use strategies for phonological awareness, fluency and comprehension. The teachers used various activities exclusively for word recognition, fluency and reading comprehension. The learners have a high level of word recognition skills, are fast readers and with an instructional level of comprehension. A positive linear relationship exists between the reading intervention strategies and the learners' level of reading skills. After the investigation on the relationship between the reading intervention strategies and learner’s reading skills, the researcher recommends the following actions.